Tantangan terhadap Privasi dan Kebebasan Berpendapat di Indonesia pada Era Digital: Analisis Pandangan Filsafat Hukum - Rasji; Muhammad Yogi Septiyan Priyono (Jurnal Hukum Lex Generalis, 2024)
This study aims to analyze the regulatory challenges and dilemmas concerning the right to privacy and freedom of expression in Indonesia’s digital era through the lens of legal philosophy. The research method employed is normative, using statutory and conceptual approaches with descriptive-analytical analysis. The digital era blurs the lines between privacy and freedom of expression, where both often intersect in online public spaces. In legal philosophy, privacy is not only a personal sphere but also a domain shaped by state and institutional power through digital surveillance. Meanwhile, freedom of expression, while foundational to democracy, is vulnerable to misuse for spreading hate speech or disinformation. Indonesian law recognizes these rights through constitutional and statutory guarantees, yet their implementation faces structural and technical challenges. Legal philosophy plays a critical role in balancing these rights by emphasizing justice, legal morality, and human dignity. In conclusion, a reform of digital law is needed—one that is not only technically adaptive but also grounded in ethical and philosophical values to ensure equal protection of privacy and freedom.